Atmospheric Microplastics Characterization Methodology - Lorgio G. Valdiviezo-Gonzales; Paola Ortiz-Ojeda; Gabriel De-la-Torre; Fernando García; Nereida Llerena (Chemical Engineering Transactions)
Microplastics (MPs) are considered emerging pollutants, whose presence has been reported in various ecosystems. Therefore, many studies have been reported evaluating the presence of MPs in air, soil and water. However, there is still a lack of clear methodologies that allow the identification, quantification and characterization of these contaminants. This study aims to develop a methodological guide for the evaluation of atmospheric MPs. The methodology presented is based on a comprehensive review of previous studies as well as the authors' expertise in the analysis of MPs in settleable atmospheric dust samples and other matrices. The guide provides detailed protocols for material handling, sampling, sample digestion, density separation, and physical and chemical characterization of MPs. Each methodological step is clearly outlined and supported with photographs, facilitating a comprehensive and practical understanding of the procedures. Furthermore, the proposed methodological framework applies to both indoor and outdoor samples collected via active sampling methods. The findings presented in this study are intended to serve as a valuable resource for researchers interested in developing MPs-related studies. Future research should focus on method standardization, which is essential for ensuring comparability across studies and advancing regulatory frameworks addressing MPs contamination in various ecosystems.